DAY-OF-WEEK EFFECT IN THE BRAZILIAN MARKET: AN ANALYSIS FROM THE STANDPOINT OF LIQUIDITY, THE RETURN AND VOLATILITY - Ceretta, Paulo Sérgio (2010)
This study aims to verify the presence of “day-of-week effect” in the Brazilian stock market analyzing the behavior of returns, the volatility and liquidity, the latter, measured through three measures: amount of business, number of titles and financial volume. The period considered for the study was from December 1999 to December 2006, totaling 1,736 daily observations. From the estimation of the regression models with dummy variables trying to verify the presence of seasonal daily behavior. Overall, the effect day-to-week appeared on the variables significantly more liquidity than on the variables of return and volatility. Concerning the measures of liquidity, there was a seasonal behavior over the week, giving low liquidity on Monday, followed by a considerable increase on Tuesday and Wednesday, and a further reduction in Thursday and Friday. For the return, Wednesday revealed a significant positive statistically returns for the other days the average return may be considered void. The behavior of volatility proved to be quite similar throughout the week, revealing coefficients positive and significant for all the days of the week. It is worth mentioning that the average volatility of Wednesday (single day with significant returns) is not substantially different from the average volatility of the remaining days of the week.